![image](https://tex.z-dn.net/?f=6%5Ex-12%3E0+%5C%5C+6%5Ex%3E2%2A6%5E1+%7C+%3A6%5E1%5C%5C+6%5E%7Bx-1%7D%3E2)
0 \\ 6^x>2*6^1 | :6^1\\ 6^{x-1}>2" alt="6^x-12>0 \\ 6^x>2*6^1 | :6^1\\ 6^{x-1}>2" align="absmiddle" class="latex-formula">
прологарифмируем обе части по основанию 6 (6>1, знак неравенства не меняется)
![image](https://tex.z-dn.net/?f=log_66%5E%7Bx-1%7D%3Elog_62+%5C%5C+x-1%3Elog_62+%5C%5C+x%3Elog_62-1+%5C%5C+x%3Elog_62-log_66+%5C%5C+x%3Elog_6+%5Cfrac%7B2%7D%7B6%7D+%5C%5C+x%3Elog_6+%5Cfrac%7B1%7D%7B3%7D+%5C%5C+x%3Elog_6%283%29%5E%7B-1%7D+%5C%5C+x%3E-log_63++)
log_62 \\ x-1>log_62 \\ x>log_62-1 \\ x>log_62-log_66 \\ x>log_6 \frac{2}{6} \\ x>log_6 \frac{1}{3} \\ x>log_6(3)^{-1} \\ x>-log_63 " alt="log_66^{x-1}>log_62 \\ x-1>log_62 \\ x>log_62-1 \\ x>log_62-log_66 \\ x>log_6 \frac{2}{6} \\ x>log_6 \frac{1}{3} \\ x>log_6(3)^{-1} \\ x>-log_63 " align="absmiddle" class="latex-formula">
как-то так получается.